Prevalência e fatores relacionados a doença periodontal no diabetes melito gestacional e tipo 1 - Ruiz, Dóris Rocha [UNIFESP] (2010)
OBJECTIVE: The present study evaluated the relationship between periodontal disease and its clinical variables in Brazilian non-diabetic pregnant women (C), gestational diabetes mellitus (GDM), or type 1 diabetes mellitus (T1DM). SUBJECTS AND METHODS: A periodontal exam was performed in one hundred and sixty one pregnant women (GDM:80; T1DM:31; C:50) by a single blinded calibrated examiner who recorded plaque index (PI), gingival index (GI), bleeding index (BI), gingival margin location (GM), probing depth (PD), clinical attachment level (CAL), bleeding on probing (BOP), and tooth mobility index (MI). The medical variables were: age, pre-gestational body mass index (pre-BMI), fasting plasma glucose (FPG), and glycated hemoglobin (HbA1C). RESULTS: The GI, GM, PD, CAL, BOP, and MI were significantly higher (p < 0.01) among GDM and T1DM than for C. The PI was higher in GDM and similar between C and T1DM. In all groups studied, the CAL was correlated to age (rS = 0.35; p < 0.01), pre-gestational BMI (rS = 0.25; p = 0.01) and to HbA1C (rS = 0.27; p < 0.01). CONCLUSIONS: The presence of periodontal disease was significantly higher in Brazilian diabetic pregnancies (GDM and T1DM) when compared to non-diabetic pregnant women (C). The degree of periodontal disease was similar between the GDM and T1DM groups. Age, pre-gestational BMI, and HbA1C were factors which had a positive relationship with to the periodontal disease.